THE RELATIONSHIP OF MOTHER'S KNOWLEDGE ABOUT COLOSTRUM AND GIVING COLOSTRUM TO NEWBORN BABIES IN THE WORKING AREA OF THE ANDONGSARI PUSKESMAS - Hasanah, Uswatun; Purwaningrum, Yuniasih; Hidayati, Ainul (Journal of Nursing Periodic, 2025)
Introduction: The phenomenon that occurs in society is the wrong habit of mothers in breastfeeding their babies by giving milk that is already white in color and colostrum is deliberately discarded because mothers still believe the myth that colostrum is considered not part of breast milk because the color is slightly yellowish so it is not suitable for giving to babies because it can cause abdominal pain and vomiting. Avoiding giving colostrum can make babies susceptible to allergies due to lack of immune substances and cause jaundice which can cause death in babies. Giving colostrum is identical to implementing IMD. The World Health Organization (WHO) states that nationally there has been a decrease in the provision of IMD by (48.6%), while the national target for giving IMD is by (58.2%). Methods: This type of research is correlation analytic research with a retrospective approach. The research sample was mothers who had babies aged 0-1 years as many as 138 respondents from a total population of 210 using a purposive sampling technique. Univariate test results showed that the majority of respondents had less knowledge about colostrum, as many as 117 respondents (84.8%) and the majority of respondents did not give colostrum, as many as 119 respondents (86.2%). Results: The results of the bivariate test using the Mann Whitney test obtained a p value = 0.000 <0.05, so Ho was rejected, meaning that there was a significant relationship between mother's knowledge about colostrum and giving colostrum to newborns. Conclusions: Mother's good knowledge about colostrum will have an impact on giving colostrum to newborns. it is hoped that breastfeeding mothers will provide more information about colostrum and it is hoped that the health center will provide information through health education.